Transformasi Mutu Sekolah Menengah Atas: Peran Kepemimpinan, Kepengawasan, dan Kinerja Guru - Sri Wahyuni; Achmad Supriyanto; Sunarni Sunarni (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The improvement of education quality is a strategic issue in the era of global transformation, which demands effective school leadership and educational supervision systems as key factors for institutional success in achieving sustainable quality standards. This study aims to analyze the influence of school leadership and supervision on the quality of public senior high schools in East Kolaka Regency, as well as to examine the role of teacher performance as a moderating variable. The study employs a quantitative ex post facto approach with a descriptive correlational causality design. The research sample consists of 81 teachers from a total population of 138 teachers, selected through a quota sampling technique from eight public senior high schools in East Kolaka Regency. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and were then analyzed using descriptive statistics and SEM-PLS. The results indicate that school leadership, supervision, teacher performance, and school quality received positive perceptions from teachers, suggesting that leadership practices, supervision, and the professional execution of teachers’ duties have been well implemented in the schools. Inferential tests show that school leadership has a positive and significant effect on school quality, while supervision does not have a significant effect. Teacher performance was found to have a positive and significant effect on school quality but does not moderate the relationship between leadership or supervision and school quality due to the interaction values.